Pubertal delay in male nonhuman primates (Macaca mulatta) treated with methylphenidate - Mattison, Donald R. (National Academy of Sciences, 2011)
Juvenile male rhesus monkeys treated with methylphenidate hydrochloride (MPH) to evaluate genetic and behavioral toxicity were observed after 14 mo of treatment to have delayed pubertal progression with impaired testicular descent and reduced testicular volume. Further evaluation of animals dosed orally twice a day with (i) 0.5 mL/kg of vehicle (n = 10), (ii) 0.15 mg/kg of MPH increased to 2.5 mg/kg (low dose, n = 10), or (iii) 1.5 mg/kg of MPH increased to 12.5 mg/kg (high dose, n = 10) for a total of 40 mo revealed that testicular volume was significantly reduced (P < 0.05) at months 15 to 19 and month 27. Testicular descent was significantly delayed (P < 0.05) in the high-dose group. Significantly lower serum testosterone levels were detected in both the low- (P = 0.0017) and high-dose (P = 0.0011) animals through month 33 of treatment. Although serum inhibin B levels were increased overall in low-dose animals (P = 0.0328), differences between groups disappeared by the end of the study. Our findings indicate that MPH administration, beginning before puberty, and which produced clinically relevant blood levels of the drug, impaired pubertal testicular development until ∼5 y of age. It was not possible to resolve whether MPH delayed the initiation of the onset of puberty or reduced the early tempo of the developmental process. Regardless, deficits in testicular volume and hormone secretion disappeared over the 40-mo observation period, suggesting that the impact of MPH on puberty is not permanent.